2017
DOI: 10.1158/1078-0432.ccr-16-3217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel ITGαvβ6-Binding Peptide Using Protein Separation and Phage Display

Abstract: Targeted therapies are regarded as promising approaches to increase 5-year survival rate of head and neck squamous cell carcinoma (HNSCC) patients. For the selection of carcinoma-specific peptides membrane proteome of HNO97 tumor cells fractionated by the ProteomeLab PF2D system and corresponding HNO97 cells were deployed for an alternating biopanning using a sunflower trypsin inhibitor1-based phage display (SFTI8Ph) library. Stability, binding properties and affinity of novel candidates were assessed using ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 36 publications
4
56
0
4
Order By: Relevance
“…In vivo studies using the paired DX3purob6/DX3puro cell xenograft mouse model confirmed that [ 18 F]a v b 6 -BP met expectations for a v b 6 targeting and overall pharmacokinetics, with good tumor retention and kidney clearance. The tumor uptake values were similar to those noted by Altmann and colleagues for their SFITGv6 peptide which demonstrated good binding in mice bearing HNO97 xenografts (37).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In vivo studies using the paired DX3purob6/DX3puro cell xenograft mouse model confirmed that [ 18 F]a v b 6 -BP met expectations for a v b 6 targeting and overall pharmacokinetics, with good tumor retention and kidney clearance. The tumor uptake values were similar to those noted by Altmann and colleagues for their SFITGv6 peptide which demonstrated good binding in mice bearing HNO97 xenografts (37).…”
Section: Discussionsupporting
confidence: 85%
“…In vitro affinity and selectivity of [ 18 F]a v b 6 -BP for integrin a v b 6 were excellent and compared favorably with those reported by Altmann and colleagues for their SFTI-1 derivatives; however, it is noted that the experimental methods were somewhat different, and different cells lines with varying expression levels of the integrin a v b 6 were used (37). In vivo studies using the paired DX3purob6/DX3puro cell xenograft mouse model confirmed that [ 18 F]a v b 6 -BP met expectations for a v b 6 targeting and overall pharmacokinetics, with good tumor retention and kidney clearance.…”
Section: Discussionsupporting
confidence: 64%
“…This approach has been used in various applications, such as in the mapping and mimicking of epitopes, the identification of new receptors and natural ligands, high-affinity antibodies and analogs, the isolation of specific antigens binding to bioactive compounds, the production of novel enzyme inhibitors and DNA-binding proteins, and the probing of cellular and tissue-specific processes. Phage display has been successfully applied for the identification of peptides with a high specificity for target tumor neovasculature or a variety of human tumor cells (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Biotechnology Methods For Identification Of New Ligands: Dismentioning
confidence: 99%
“…When libraries based on the trypsin inhibitors sunflower trypsin inhibitor and Min23 were applied, peptides were identified by phage display as well as ribosome display for Dll4 and a v b 6 -integrin (31)(32)(33). The Dll4 peptides showed a high affinity, in the range of 4-40 nM, and a serum stability of up to 10 d. When a membrane proteome of HNO97 tumor cells (head and neck squamous cell carcinoma) fractionated by the ProteomeLab PF2D system (Beckman Coulter) and corresponding HNO97 cells for phage display with a sunflower trypsin inhibitor library were used, a novel a v b 6 -integrin-binding peptide (SFITGv6) with stability over a period of 24 h, a high affinity (diffusion constant, 14.8 nM) for a v b 6 -integrin, and an internalization ratio of 37.5% was identified (33).…”
Section: Affinity and Stability Or Scylla And Charybdis: Is There A Smentioning
confidence: 99%
See 1 more Smart Citation